Effect of ERAS pathway nursing on postoperative rehabilitation of patients undergoing gastrointestinal surgery: a meta-analysis - Fengying Dong; Yan Li; Wenxia Jin; Zhebing Qiu (BMC Surgery)
Abstract Background This study aimed to systematically evaluate the impact of the Enhanced Recovery After Surgery (ERAS) pathway on postoperative outcomes—including hospital length of stay, complication rates, readmission, reoperation, and mortality—in patients undergoing gastrointestinal surgery, to provide evidence-based guidance for clinical practice. Methods We systematically searched PubMed, Cochrane Library, Embase, Web of Science and Scopus databases for randomized controlled trials (RCTs) and cohort studies on ERAS pathway in postoperative rehabilitation. Thirteen studies comprising a total of 5,603 patients were included. Literature screening and quality assessment followed the standards of Cochrane Collaboration and Newcastle-Ottawa scales. Statistical analysis was performed using R software to calculate the relative risk (RR), mean difference (MD) with 95% confidence interval (CI), and heterogeneity through the I² statistic, with significance set at P < 0.05. This systematic review and meta-analysis has been registered in the PROSPERO database (ID: CRD42024608876). Results The ERAS pathway significantly shortened the postoperative hospital stay (MD = -3.16, 95% CI [-4.10, -2.21], P < 0.01) and reduced the incidence of postoperative complications (RR = 0.70, 95% CI [0.58, 0.84], P < 0.01). It also significantly reduced the readmission rates (RR = 0.75, 95% CI [0.58, 0.96], P = 0.02). However, there was no statistically significant difference in the impact of ERAS pathway on reoperation rate and mortality (RR = 0.59, 95% CI [0.01, 30.14], P = 0.62). Conclusions ERAS protocols are associated with improved postoperative recovery in gastrointestinal surgery, including shorter hospital stays and reduced complication and readmission rates. Although no significant effects were found for reoperation or mortality, the overall evidence supports the broader clinical adoption of ERAS, with a need for further high-quality studies to address remaining uncertainties.